下顎正中部に生じた明細胞性歯原性癌の1例 - 加藤, 雄大; 林, 祐太郎; 渡邉, 賀子; 増本, 一真; 加藤, 文度; 長田, 哲次 (日本口腔外科学会雑誌, 2018)
Clear cell odontogenic carcinoma (CCOC) is a rare intraosseous tumor of the jaw that was classified as a malignant odontogenic tumor by the WHO classification in 2005. Although 104 cases have been reported in the literature to date, there are no common treatments or prognostic factors. We report a new case of CCOC in a patient who underwent reconstruction using a vascularized free fibula flap.　A 63-year-old man with tooth mobility and swelling of the middle lingual side of the mandible came to our clinic. He did not complain of pain. Enhanced computed tomography (CT) revealed a 45 × 35 × 33 mm tumor in the mandibular bone associated with an osteolytic lesion. Furthermore, invasion of the mylohyoid and genioglossus muscle was observed on magnetic resonance images (MRI). Since malignancy was suspected on biopsy, we performed wide tumor resection and reconstruction with a vascularized free fibula flap. Finally, CCOC was diagnosed on by histopathological examination. As of 3 years 10 months after the operation, neither recurrence nor metastasis was detected.